Memória e identidade : o processo de sucessão e herança no Mercado Municipal de Montes Claros - MG, Brasil - Dias Guimaraes, Thaynara Thaissa; Doula, Sheila Maria (2018)
This research aimed to understand the social representations about the process of succession and inheritance of tents and marketer profession in the Municipal Market of Montes Claros - MG, Brazil. It is used the qualitative methodology with literature review and documentary research. Also were used for data collection semi-structured interviews conducted in depth with a total of 8 marketers. Through the results it was observed that the transmission of the marketer profession is a process that happens in everyday life, through the memory evocation design and practices that run through generations. On the other hand, the transmission of the material heritage is bonded to economic management and the history of families
Esta pesquisa visa compreender as representações sociais sobre o processo de sucessão e herança das barracas e da profissão de feirante no Mercado Municipal de Montes Claros - MG, Brasil. Utiliza-se a metodologia qualitativa com pesquisa bibliográfica, pesquisa documental e entrevistas semi estruturadas com um total de 8 feirantes. Através dos resultados conclui-se que a transmissão da profissão de feirante é um processo que se desenvolve no cotidiano, através da evocação da memória e de práticas que perpassam gerações. Por sua vez, a transmissão do patrimônio material está vinculada à gestão econômica e à história das famílias
Keywords: Brazil; Social representations; Patrimony; Municipal market; Brasil^lpt; Representações sociais; Patrimônio; Mercado municipal